The basics of cyber safety : computer and mobile device safety made easy - Sammons, John (Cambridge, MA : Syngress is an imprint of Elsevier, 2017)
"The Basics of Cyber Safety: Computer and Mobile Device Safety Made Easy presents modern tactics on how to secure computer and mobile devices, including what behaviors are safe while surfing, searching, and interacting with others in the virtual world. The book's author, Professor John Sammons, who teaches information security at Marshall University, introduces readers to the basic concepts of protecting their computer, mobile devices, and data during a time that is described as the most connected in history. This timely resource provides useful information for readers who know very little about the basic principles of keeping the devices they are connected to--or themselves--secure while online. In addition, the text discusses, in a non-technical way, the cost of connectedness to your privacy, and what you can do to it, including how to avoid all kinds of viruses, malware, cybercrime, and identity theft. Final sections provide the latest information on safe computing in the workplace and at school, and give parents steps they can take to keep young kids and teens safe online. Provides the most straightforward and up-to-date guide to cyber safety for anyone who ventures online for work, school, or personal use Includes real world examples that demonstrate how cyber criminals commit their crimes, and what users can do to keep their data safe"--Provided by publisher.
What is cyber safety? -- Before connecting to the Internet -- Software problems and solutions -- Email safety and security -- Cybercrime -- Protecting yourself on social media -- Finding a job online -- Protecting your reputation -- Beyond technology: dealing with people -- Protecting your kids.
Includes bibliographical references and index.
Keywords: Cyber intelligence (Computer security); Computer networks -- Security measures; Internet -- Security measures; Computer security